Normobaric hyperoxia plays a neuroprotective role after cerebral ischemia by maintaining the redox homeostasis and the level of connexin43 in astrocytes. (14th June 2022) - Qi, Zhifeng; Yuan, Shuhua; Liu, Ke Jian; Ji, Xunming
Abstract: Introduction: Acute cerebral ischemia is caused by an insufficient blood supply to brain tissue. Oxygen therapy, which is able to aid diffusion to reach the ischemic region, has been regarded as a possible treatment for cerebral ischemia. Recent animal and pilot clinical studies have reported that normobaric hyperoxia (NBO) showed neuroprotective effects if started soon after the onset of stroke. However, little is known about the role and mechanism of NBO treatment in astrocytes. Connexin43, one of the main gap junction proteins in astrocytes, is extremely sensitive to hypoxia and oxidative stress after cerebral ischemia. Aims: In the present study, we used sutures to develop an ischemia/reperfusion model in rats to mimic clinical recanalization and investigated the role of connexin43 in NBO‐treated stroke rats, as well as the underlying mechanism of NBO therapy. Results: Normobaric hyperoxia treatment maintained the homeostasis of oxidoreductases: glutathione peroxidase 4 (GPX4) and NADPH oxidase 4 (two important oxidoreductases) and rescued the ischemia/reperfusion‐induced downregulation of connexin43 protein in astrocytes. Furthermore, NBO treatment attenuated cerebral ischemia‐induced cytochrome c release from mitochondria and was involved in neuroprotective effects by regulating the GPX4 and connexin43 pathway, using Ferrostatin‐1 (an activator of GPX4) or Gap27 (an inhibitor of connexin43). Conclusions: This study showed the neuroprotective effects of NBO treatment by reducing oxidative stress and maintaining the level of connexin43 in astrocytes, which could be used for the clinical treatment of ischemic stroke. Abstract : Acute ischemic stroke impairs the redox balance [decreasing glutathione peroxidase 4 (GPX4) and increasing NADPH oxidase 4 (NOX4)] and reduces the connexin43 expression in astrocytes, leading to mitochondrial damages and cerebral injury. Normobaric hyperoxia (NBO) plays a neuroprotective role by reducing oxidative stress and maintaining the level of connexin43 in astrocytes.